Meningkatkan Kemampuan Bernalar Kritis, Dengan PBL Materi Gaya Hidup Sehat Fase F, SMK Negeri 1 Merdeka - Kuntum Br Sinuhaji (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Education in Indonesia faces various complex challenges. Therefore, efforts continue to be made by the government, educational institutions and society as a whole to improve access, quality and relevance of education in order to create a young generation that is skilled, competitive and ready to face global challenges. In the context of the Independent Curriculum, Catholic religious education in Indonesia focuses on developing religious understanding, moral values and Catholic spirituality for students. The independent curriculum emphasizes the Pancasila student profile. In this classroom action research, the researcher focuses on the critical reasoning dimension which is based on the importance of forming strong character and mental attitudes in the younger generation, especially in facing complex global challenges. The majority of students who are accepted to school at SMK Negeri 1 Merdeka are students who are accepted into majors that do not match their initial interests. Students with this kind of condition tend to feel unmotivated to learn. Based on the problem conditions above, teachers can provide learning experiences by designing the learning process. One learning model that can be applied is Problem Based Learning (PBL) or problem-based learning. The research objectives include (1) to find out how the use of the Problem Based Learning model in increasing students' learning motivation on healthy lifestyle material, in class xi of SMK Negeri 1 Merdeka, (2) to find out how to increase the learning motivation of class assistance with the Problem Based Learning model in healthy lifestyle material, (3) to find out the use of the Problem Based Learning model in healthy lifestyle material, class XI students at SMK Negeri 1 Merdeka can apply the Pancasila student profile in healthy lifestyle material, critical reasoning principles. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research used observation, interviews and documentation. data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from research results that refer to the problem formulation. The use of the Problem Based Learning model according to the syntax which includes orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem solving process, is effective in helping increase learning motivation and student independence in Healthy lifestyle material in class XI of SMK Negeri 1 Merdeka